'Transforming Labour' at the Westrail Workshops, Midland, WA, 1960s to 1990s - Oliver, Bobbie (2003)
The paper identifies ways in which labour was transformed at the Westrail Workshops, Midland, WA, from the 1960s to the 1990s. It examines the change from steam to diesel locomotives and the resulting impact on the various skilled trades, and the implementation of better health and safety practices. The paper discusses ways in which these changes affected the apprenticeship structure and examines whether safer, more inclusive work practices empower workers, making them more in control of their work place and their future.